Structure of Fish Community in The Alas River of Aceh Tenggara District - Hesty Wahyuningsih (Talenta Publisher, 2021)
Research on the Community Structure of Fish on the Alas River in Babul Makmur sub-district Aceh Tenggara district was conducted from April to October 2018. The aim of this research was to analyze the structure of fish communities and to analyze physical-chemical factors related to fish community structures in the water of the Alas River in Babul Makmur sub-district Aceh Tenggara district. This research using